Nanocomposite TiAlBN Coatings As A Corrosion Protection Layer For AZ91 Mg Alloy Substrate In NaCl - Zainal Abidin, Muhammad Zaimi; Mohd Rosli, Zulkifli; Mohamad Juoi, Jariah; Mahamud, Zainab (Trans Tech Publications, 2015)
Magnesium alloys create increasing interest in structural application where weight reduction is vast concern. However,one of magnesium drawback in various applications is low corrosion resistance.In general,a hard coating can be applied on metal to combat such a problem.AlN and TiN coatings are most widely utilized in manufacturing area i.e for structural application due to its high hardness, high chemical stability,and excellent adhesion to substrates.Most recent,TiAlBN coating catch many attentions due to its superior properties than other most studied hard coating.The incorporation of aluminium in the cubic face centered TiN structure on Ti sites leads to deformation and strengthening of the crystal structure of the coating together.Moreover,incorporation of BN in this coating should improve and enhanced the corrosion resistance of Mg alloy.Therefore,in this study,TiAlBN coating have been chosen to be deposited on Mg alloy using reactive magnetron sputtering together with AlN and TiN coatings for comparison study.During depositions, target power,working pressure and bias voltage are optimized for each coating.Analysis on the effect of AlN, TiN and TiAlBN coatings on Mg alloy substrate include thickness measurement and microstructure by scanning electron microscope (SEM).Coatings phase were analysed using glancing angle X-ray diffraction analysis (GAXRD) and corrosion properties were evaluated using potentiodynamic polarization in NaCl solution.TiAlBN shows better performance of corrosion protection with the least corrosion rate (penetration rate = 0.20 mm/yr;mass loss rate=0.97g/m2d) in sodium chloride (NaCl) solution although having the lowest coating thickness (412 nm).